Review of selected performance measurement models used in public administration - Alicja Gębczyńska; Renata Brajer-Marczak (Administrative Sciences, 2020)
The main goal of this article is to define the characteristics of and to evaluate the three selected models used to measure the performance of public administration bodies, with an emphasis placed on their application in different perspectives. The contemporary public administration institutions are obligated to increase their operating efficiency as well as the satisfaction of their stakeholders. This is precisely why they have been implementing diverse models, especially those already used for years in managing profit-oriented organisations. The models chosen for analysis are applied in public administration, making it possible to measure numerous indicators of both financial and nonfinancial nature. The research method adopted by the authors is a conceptual literature review performed using the resources of the Scopus, Springer, WoS, Emerald, and EBSCO databases. The items subject to analysis were the 3Es (i.e., economy, efficiency, effectiveness) and IOO (e.g., input, output, and outcome) models as well as the model included in the BSC (Balance Scorecard). The research has evidenced that each of the models has its strengths and limitations. The results thus obtained have led to a conclusion that the solution showing the highest potential in the area of the study is the performance measurement model proposed under the BSC; however, according to the authors, it still requires some fine-tuning to public administration's operating conditions and organisational culture. The article also highlights the fundamental operationalisation problems related to the subject in question.
Keywords: 350; public administration; performance measurement models; performance